2008
DOI: 10.1007/s10393-007-0148-7
|View full text |Cite
|
Sign up to set email alerts
|

A Landscape-based Model for Predicting Mycobacterium ulcerans Infection (Buruli Ulcer Disease) Presence in Benin, West Africa

Abstract: Mycobacterium ulcerans infection (Buruli ulcer [BU] disease) is an emerging tropical disease that causes severe morbidity in many communities, especially those in close proximity to aquatic environments. Research and control efforts are severely hampered by the paucity of data regarding the ecology of this disease; for example, the vectors and modes of transmission remain unknown. It is hypothesized that BU presence is associated with altered landscapes that perturb aquatic ecosystems; however, this has yet to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
38
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 37 publications
7
38
0
2
Order By: Relevance
“…To date, the use of land cover and landscape pattern metrics as predictors for BU presence or risks has been explored. 7,9,30 However, studies on the relationship between landscape diversity and BU disease are still rare. Brou and others 8 reported that landscape diversity was related to BU in Cote d'Ivoire.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the use of land cover and landscape pattern metrics as predictors for BU presence or risks has been explored. 7,9,30 However, studies on the relationship between landscape diversity and BU disease are still rare. Brou and others 8 reported that landscape diversity was related to BU in Cote d'Ivoire.…”
Section: Discussionmentioning
confidence: 99%
“…La taille du foyer est validée si la probabilité d'apparition d'un nouveau cas est plus importante dans le foyer qu'à l'extérieur par l'analyse de la dispersion de l'apparition de tous les cas sur le territoire. Cette méthode a été validée dans des études du lien spatio-temporel entre l'environnement et des foyers de maladies vectorielles ou non (Johnson, 2006, Hsu, 2007Wagner, 2008).…”
Section: Les Effets De Contexte à La Réunionunclassified
“…Even though the infection affects all age groups, at least half of all cases occur in children under age 15 years (3). More than 30 countries worldwide have reported (but not always confirmed) this emerging disease, with the highest incidence in West and Central Africa, where the disease occurs in foci among people living in rural marshes, wetlands, and riverine areas (1,4). As proximity to these slow-flowing or stagnant water bodies is a known risk factor for M. ulcerans infection (5) and as M. ulcerans DNA has been detected in a variety of aquatic specimens (6,7), it is generally believed that M. ulcerans is an environmental mycobacterium that can initiate infection after microtraumata of the skin (8).…”
mentioning
confidence: 99%